2018
DOI: 10.1302/2058-5241.3.170020
|View full text |Cite
|
Sign up to set email alerts
|

Spine–hip relations in patients with hip osteoarthritis

Abstract: Patients with hip osteoarthritis often have an abnormal spine-hip relation (SHR), meaning the presence of a clinically deleterious spine-hip and/or hip-spine syndrome.Definition of the individual SHR is ideally done using the EOS® imaging system or, if not available, with conventional lumbopelvic lateral radiographs.By pre-operatively screening patients with abnormal SHR, it is possible to refine total hip replacement (THR) surgical planning, which may improve outcomes.An important component of the concept of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 44 publications
1
44
0
Order By: Relevance
“…My understanding of the current model of MACC is that most trunnions are properly engaged at the time of implantation, and corrosion and/ or fretting does not occur until some point after the hip has been in service. This notion is supported by prior publications from our center [2,4,7], the aforementioned work from Levine et al [8], and historic and contemporary retrieval lab observations that show corrosion in only some specimens [9,10]. On the contrary, the investigators' experience seems to show metal ion production in all noncontrol specimens, even at an early time frame.…”
Section: Letter To the Editor On "Cobalt And Chromium Ion Release In supporting
confidence: 75%
See 1 more Smart Citation
“…My understanding of the current model of MACC is that most trunnions are properly engaged at the time of implantation, and corrosion and/ or fretting does not occur until some point after the hip has been in service. This notion is supported by prior publications from our center [2,4,7], the aforementioned work from Levine et al [8], and historic and contemporary retrieval lab observations that show corrosion in only some specimens [9,10]. On the contrary, the investigators' experience seems to show metal ion production in all noncontrol specimens, even at an early time frame.…”
Section: Letter To the Editor On "Cobalt And Chromium Ion Release In supporting
confidence: 75%
“…The original cohort patients had newonset symptoms with prior well-functioning THAs, and many patients underwent revision surgery with a high rate of complications [3], as the authors describe in their article. More recently, I have noted a high incidence of asymptomatic serum cobalt (Co) elevation in a portion of the original population [4]. Therefore, understanding the details and implications of the current work is critical for my patients.…”
Section: Letter To the Editor On "Cobalt And Chromium Ion Release In mentioning
confidence: 99%
“…Conventional preoperative two-dimensional (2D) templating of the pelvis with the patient in the standing position may therefore not account for patient-specific safe zones for implant positioning. 27 Suboptimal implant positioning in THA leads to increased risk of hip instability, accelerated wear of the bearing surface, and reduced long-term implant survivorship. 2224…”
Section: Conventional Manual Techniques For Thamentioning
confidence: 99%
“…In addition, it is a biomechanical marker to estimate the potential sagittal pelvic range of motion (ROM). 18 , 19 Previous studies showed that PI is on average 50° (range, 34° to 84° ) and corresponds to the sum of the sacral slope (SS) and the pelvic tilt (PT). 20 , 21 SS and PT are dynamic parameters defined as postural angles, and they change through the different pelvic positions (standing and sitting).…”
Section: Sagittal Spinopelvic Anglesmentioning
confidence: 99%